Improving school-age children's knowledge about the ethics of coughing and sneezing - Umairahmah, Nafa; Romlah, Siti; Finarti, Dian Rizeki; Susilawati, Susilawati; Faiqatul, Nainie; Nahdah, Nahdah; Ratnasari, Lina; Tyas, Eka Suryaning; Wieminaty, Aldi Febrian; Azmi, Liza Ulil; Yuniardiningsih, Erisa; Erynda, Revina Fiandany; Hanifah, Siti Nur; Sasmito, Priyo (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Coughing is a natural defense mechanism that helps clear the respiratory tract of irritants and pathogens. In addition to being a necessary physiological reflex, coughing can also be caused by diseases that attack the respiratory tract, such as tuberculosis, asthma, pneumonia, acute respiratory infections, and other respiratory diseases. Transmission of the disease occurs when an infected person releases these droplets, which can be inhaled by others. Purpose: To determine the effectiveness of flip chart-based health education in improving children's knowledge about coughing and sneezing etiquette. Method: Pre-experimental quantitative research design with a one-group pretest-posttest design approach. The sample was selected through total sampling involving Al-Huda Elementary School, Jember. This research was conducted in October-December 2024. The independent variable in this study is the use of flip charts, while the dependent variable is knowledge of cough etiquette. The instrument used was a questionnaire on knowledge of coughing and sneezing etiquette consisting of 10 multiple-choice questions. Results: The average age of the participants was 8.4 years with a standard deviation of 1.0 in the age range of 7-10 years. The number of male and female participants had the same percentage of 12 participants (50%). The average pre-test score was 55.8 with a standard deviation of 25.7, while the post-test score increased to 75.0. Statistical calculations revealed a z value of -3.7 and a significance level (2-tailed) of less than 0.001. This indicates a significant increase in knowledge of cough etiquette pre-post test. Conclusion: Flip chart media is an effective educational tool to improve children's knowledge about coughing and sneezing etiquette. By providing structured, interesting, and visually appealing content, flip charts improve learning outcomes and contribute to the implementation of better health behaviors.